ANALYSIS OF PROPERTIES OF CONCRETE USING SEA SHELLS CRUSHEDPOWDER AS ADMIXTURE - Gadgihalli, Vishal; Meena; Lohit; HavanjeDinakar, Raghavendra Prasad; Babitha Rani (International Journal of Research -GRANTHAALAYAH, 2017)
The tremendous increment of demand on concrete made admixture one of major component. As admixtures help in enhancement of concrete physical and chemical admixture. In this paper analysis of sea shells as chemical admixture is studied and verified the strength of concrete and temperature emitted due to chemical reaction to the normal Portland cement. As sea shells contain calcium carbonate, CaCo3 as major composition, as calcium is one major component that helps in densifying and hardening of bones in all living things. The flexural and compressive strength has gradually increased; the transmission temperature and reduction time of exothermal reaction has reduced. Hence seashell acts as great admixture.